Enhancing Early Reading Skills Through Literacy Alphabet Cards: An Innovative Solution for Elementary Students - Sufanti, Main; Noviafitri, Kartika Satya; Rifa, Sabrina Khoir (International Journal of Elementary Education, 2024)
The issue of low early reading proficiency among students is the primary focus of this study. This research aims to analyze the factors influencing students' reading difficulties, describe the implementation of the Literacy Alphabet Cards (KAL) as a learning medium in early-grade classrooms, and present the outcomes of its application in teaching. A qualitative research method with a descriptive design was employed. Data collection techniques included observations, interviews, and the direct involvement of the researcher in the learning process. Data were analyzed using an interactive data analysis technique encompassing data collection, data reduction, data presentation, and conclusion drawing with verification. The findings reveal internal factors affecting reading difficulties, such as intelligence levels and learning motivation, as well as external factors, including family and community environments. The KAL medium was designed using simple materials and implemented directly during the teaching process. The application of the KAL medium proved effective in enhancing early reading skills, as evidenced by improvements in students’ learning outcomes. The study concludes that the KAL medium can serve as an innovative alternative to addressing early reading difficulties by incorporating approaches that consider both internal and external student factors.